Differences in Knowledge of Women of Fertilizing Age Before and After Education About Breast Self Examination Using Video in The Selabih Village Tabanan - Ni Made Ayu Adiani; Ni Made Dwi Mahayati; Ni Made Dwi Purnamayanti (JURNAL KEBIDANAN KESTRA (JKK), 2024)
The high number of cases of non-communicable diseases is the main cause of death in Indonesia in 2020, one of which is breast cancer. The problem of breast cancer in Indonesia can be overcome through breast self-examination. The aim of this research was to determine the difference in knowledge of women of childbearing age before and after education about breast self-examination using video in Selabih Village Tabanan. This research includes research Quasi Experimental by design One Group Pretest-Posttest. The number of samples used was 53 women of childbearing age. Data collection includes filling out a knowledge questionnaire pretest and posttest. Before being given education, the median score was 85 with score range of 65-100 and after being given education the median score increased to 90 with score range of 80-100. Analysis results used tests wilcoxon show p-value of 0.000 which can be concluded that there is a difference in knowledge of women of childbearing age before and after education about breast self-examination using video. The use of this educational video should be continued by midwives at local health centers as a medium of education for women of childbearing age so that they are able to do BSE regularly.